Notions of Maritime Green Supply Chain Management - Fairuz, Jasmi; Fernando, Yudi (IGI Global USA, 2018)
Maritime supply chain is arguably the most imperative service sector for facilitating intercontinental trade globally. Within these complex supply chain systems, shipping organizations, port authorities and import-export firms naturally a collaborator and cooperates with each other in the broader management context of maritime logistics. Meanwhile, increasing environmental concerns have forced global maritime organizations to implement sustainability in their operation. MGSCM is a recent focus within the sustainable supply chain body of literature with ample room for understanding its challenges and opportunities. With that in mind, the objective of this paper is to review the literature on the development of GSCM and conceptualizing the notion of MGSCM concept in maritime context derived from GSCM respectively. This paper is unique because it addresses the complex dimension of ‘‘sustainability'' in maritime supply chain and try to define it in line with existing GSCM context. The findings of this paper show that GSCM can be extended into maritime perspective to define MGSCM.